The effects of oral nutritional formula enriched with arginine, omega 3 fatty acids and nucleotides on methotrexate-induced experimental intestinal mucositis - Yilmaz Akyuz, Elvan; Akyuz, Cebrail; Kiziltan, Gul; Sehirli, Ahmet Ozer; Cetinel, Sule (Progress in Nutrition, 2018)
The aim of this study to investigate the effect of an immunonutritional (IN) oral formula enriched with arginine, omega-3 fatty acids and nucleotides in methotrexate (MTX)-induced experimental intestinal mucositis model. In the study, 32 rats were divided into four groups consisting eight animals in each. Control group fed for 5 days with only saline with gavage, IN group fed for 5 days with an oral IN formula three times a day, MTX group with an intraperitoneal single dose MTX (20 mg/kg), followed by saline with gavage, MTX-IN group with a single dose of MTX, followed by an oral IN formula three times a day. The blood and jejunal tissue sample were collected and then the rats were sacrificed on the sixth day of the study. The level of TNF-α, IL-1β in serum, luminol, lusigenin, glutathione, myeloperoxidase, malondialdehyde and Na-K+ATPase in the jejunal tissue samples were analyzed. Histopathological examination was performed in the jejunal tissue samples. In the MTX group, TNF-α, IL-1β levels in serum, and luminol, lusigenin, malondialdehyde levels, and myeloperoxidase activity in tissue samples were found significantly higher than the control group. Glutathione and Na-K+ATPase levels were lower in the jejunal tissue of the MTX group compared to control group. However, the supplementation of IN with the MTX resulted in a significant increase in glutathione and Na-K+ATPase levels. Severe epithelium loss and inflammatory cell increase were observed in the MTX group on histological examination, whereas these parameters were regressed in the MTX-IN group. Increasing in the mitosis rate of enterocytes and inflammatory cell density decreased with the IN. In conclusion, this study shows that chemotherapy has adverse effects on intestinal mucosa and the IN formula has a protective effect of on MTX-associated intestinal damage.